Antioxidant effect of grape seed extract corrects experimental autoimmune encephalomyelitis behavioral dysfunctions, demyelination, and glial activation - Mabrouk, Maha; El Ayed, Mohamed; Démosthènes, Amélie; Aissouni, Youssef; Aouani, Ezzedine; Daulhac-Terrail, Laurence; Mokni, Meherzia; Bégou, Mélina (Frontiers in Immunology, 2022)
Background and purpose Multiple sclerosis (MS), a multifactorial autoimmune disease of the central nervous system (CNS), is characterized by demyelination and chronic inflammation, as well as axonal and neuronal loss. There is no cure for MS, and despite a significant improvement in the therapeutic management of patients during the last 20 years, some symptoms are still resistant to treatment, and the evolution of the disease to progressive form seems still ineluctable. The etiology of MS is complex and still not fully understood. However, inflammation is a major driver of physiopathology and oxidative stress contributes to CNS lesions and promotes existing inflammatory response. Plant polyphenols are endowed with many therapeutic benefits through alleviating oxidative stress and inflammation, thus providing neuroprotection in MS. We presently evaluated the curative effect of grape seed extract (GSE) in an experimental autoimmune encephalomyelitis (EAE) mouse model of MS. Experimental approach Six-week-old C57Bl/6J females were subjected to the EAE paradigm (using myelin oligodendrocyte glycoprotein peptide fragment (35-55), complete Freund’s adjuvant, and pertussis toxin) and then chronically treated with GSE from day 10 to day 30 post-induction. Clinical score and body weight were monitored daily, while evaluation of sensitive, motor, cognitive, and anxiety-related behaviors was performed weekly. Then, the GSE effect was evaluated on whole brain and spinal cord samples through the evaluation of oxidative stress damage, antioxidant capacities, myelin alteration, astroglial and microglial proliferation, and sirtuin expression. Key results Grape seed extract curative chronic treatment corrected the clinical course of EAE, as well as the mechanical hypersensitivity, and avoided the development of EAE mouse thermal cold allodynia. The neuropathological evaluation showed that GSE reduced oxidative stress in the brain and spinal cord by decreasing the lipid and protein oxidation through correction of the three main antioxidant enzyme activities, namely, superoxide dismutase, catalase, and glutathione peroxidase, as well as restoring normal myelin protein expression and correcting microglial and astroglial protein overexpression and sirtuin downregulation. Conclusion and implications These data strongly support GSE as an effective therapeutic approach in MS treatment.